Adoption factors and implementation steps of ITSM in the target organizations - Sahibbudin, Shamsul (Elsevier, 2009)
ITIL is the most widely used IT framework in most organizations nowadays. Many public and private IT organizations have good impressions and attempt to adopt ITIL into their own businesses. However, the ITIL implementation faces some issues by the target organizations to accept this as a complete framework. In addition, there are several steps to implement this framework in the target organizations. This paper tries at first to clarify each of these major issues and then suggest a mature guideline on the implementation of ITIL in the target organizations.